The Impact of the Determination of PKN Surakarta and its Surroundings on the Subosukawonosraten Development Area - Mudzakir, Aditya Muhammad; Indriani, Fera; Ramadhan, Muhammad Daiyan (Universitas Gorontalo, 2025)
This study combines growth center theory, basic sector concept, and shift-share analysis to evaluate the impact of the establishment of the National Activity Center (PKN) of Surakarta and its surroundings on the Subosukawonosraten Development Area. The results show that the policy of determining the national activity center in the city area tends to increase economic growth, however, the hierarchical structure of the national urban system must be considered. The application of Functional Urban Area (FUA) emerges as a solution to support economic growth and sustainability, with infrastructure being the key driver. The analysis of basic economic sectors shows that the policy of establishing PKN Surakarta affects the growth of the industrial sector, especially in the area around Subosukawonosraten. Surakarta City becomes the center of service sector activities, while the surrounding areas develop in the industrial sector. The result also differentiates the development of economic base between the areas designated as Regional City Center (PKW) and Local City Center (PKL).